Deep Learning untuk Solusi Cerdas: Workshop Penggunaan Aplikasi AI untuk Kehidupan Sehari-Hari - Netti Herawati; K Ghazali; Uci Suryani; M Bambang Purwanto (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity is motivated by the rapid development of deep learning and artificial intelligence (AI) which has penetrated various aspects of life. Prasetiya Mandiri Polytechnic held a workshop